Preliminary results of coccolithophore evidence for the direct influence of Black Sea waters inflow into the N. Aegean Sea - Karatsolis, B.; Triantaphyllou, M.; Dimiza, M.; Psarra, S.; Birli, A.; Mara, P.; Lagaria, A.; Gogou, A. (11th Panhellenic Symposium on Oceanography and Fisheries, 2015)
A study on living coccolithophores from the euphotic zone is conducted in the northeastern Aegean Sea, an area under the direct influence of the Black Sea waters inflowing into the Aegean. A total of 53 plankton samples from 5 stations have been collected during four sampling periods between 2011 and 2014. High concentrations of Emiliania huxleyi and low concentrations of oligotrophic species, such as holococcolithophores, are indicative of a direct influence of the Black Sea waters inflow on the coccolithophore assemblages in the northeastern Aegean Sea.